Growth of Companies: Empirical Study of the Companies Listed in Developing Economies : Pertumbuhan Perusahaan: Studi Empiris Perusahaan Yang Terdaftar di Negara Berkembang - Tariq Tawfeeq Yousif Alabdullah (Universitas Muhammadiyah Sidoarjo, 2020)
The aim of this study is to investigate the impact of some control determinants on growth of companies as a reflection to an economic perspective. The methodology used in the current study is cross sectional for a sample of companies belonging to industrial and service sectors (non-financial sector) for the year of 2019 in developing economies. We find a positive link between a number of board members and companies’ growth, while leadership position has insignificant link to companies’ growth. This means that an important policy implication should be considered by policy makers and management in the companies to increase numbers of members in the board of directors which is worth towards enhancement of companies’ growth. The value and originality of this study lies in its results that should be taken into account by several interested parties such as the management in the companies who engage in behavior that leads to maintaining strong control determinants, and also the financial analysts who manage studies on control determinants to enhance companies' growth and further the policymakers who design and implement plans of such determinants.